Electrodeposited Iridium Oxide on Carbon Fiber Ultramicroelectrodes for Neural Recording and Stimulation. Issue 9 (1st January 2018) - Deku, Felix; Joshi-Imre, Alexandra; Mertiri, Alket; Gardner, Timothy J.; Cogan, Stuart F.
Abstract : Host encapsulation decreases the ability of chronically implanted microelectrodes to record or stimulate neural activity. The degree of foreign body response is thought to depend strongly on the cross-sectional dimensions of the electrode shaft penetrating neural tissue. Microelectrodes with cellular or sub-cellular scale shaft cross-sectional dimensions, such as carbon fiber ultramicroelectrodes have been previously demonstrated to elicit minimal tissue response, but their small geometric surface area results in high electrode impedances for neural recording, and reduced charge injection capacity during current pulsing for neural stimulation. We investigated electrodeposited iridium oxide films (EIROF) on carbon fiber ultramicroelectrodes as a means of enhancing the charge injection capacity and reducing electrode impedance. EIROF coatings reduced the electrode impedance measured at 1 kHz by a factor of 10 and improved charge storage and charge injection capacities. The maximum charge injection capacity was also strongly dependent on the interpulse bias and pulse width, and reflected a potential-dependent EIROF impedance. The charge injection capacity of the EIROF-coated carbon fiber ultramicroelectrodes measured in an inorganic buffered saline model of interstitial fluid exceeded 17 mC/cm 2 with appropriate biasing, allowing charge-injection at levels well above reported charge/phase thresholds for intraneural microstimulation.